Modulation of autoimmune pathogenesis by T cell-triggered inflammatory cell death - Katsuhiro Sasaki (Nature Portfolio, 2019)
Many forms of autoimmune disorder involve abnormal T cell functions, but how this versatility is achieved is not fully clear. Here the authors show that Sharpin-deficient Treg cells induce the death of local keratinocytes via multiple programmed cell death and innate inflammation to cause skin inflammation similar to cpdm mice with genetic deletion of Sharpin.